2015
DOI: 10.1186/s13028-016-0215-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum 8-hydroxy-2-deoxyguanosine as a marker of DNA oxidative damage in horses with recurrent airway obstruction

Abstract: BackgroundIt has been reported that equine recurrent airway obstruction (RAO) is a state of oxidative stress. Oxidant-antioxidant imbalance is known to increase the conversion of deoxyguanosine to 8-hydroxy-2-deoxyguanosine (8-OHdG) in DNA. 8-OHdG can easily be measured using ELISA tests in serum or urine samples. In this study, we analysed serum 8-OHdG levels in horses with recurrent airway obstruction and in healthy controls.ResultsThe study material consisted of seven healthy horses and seven horses with sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The levels of 8-OHdG were evaluated using a commercial enzyme-linked immunosorbent assay (ELISA) kit (Highly Sensitive 8-OHdG Check ELISA; Fukuroi, Shizuoka, Japan), as previously described. 24 25 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of 8-OHdG were evaluated using a commercial enzyme-linked immunosorbent assay (ELISA) kit (Highly Sensitive 8-OHdG Check ELISA; Fukuroi, Shizuoka, Japan), as previously described. 24 25 …”
Section: Methodsmentioning
confidence: 99%
“…The levels of 8-OHdG were evaluated using a commercial enzyme-linked immunosorbent assay (ELISA) kit (Highly Sensitive 8-OHdG Check ELISA; Fukuroi, Shizuoka, Japan), as previously described. [24][25] Sperm chromatin structure assay (SCSA) SCSA measures the susceptibility of sperm DNA to acid-induced denaturation in situ by using the metachromatic properties of acridine orange (AO). By quantifying this metachromatic shift of AO from green to red after acid treatment using flow cytometry, the extent of DNA denaturation can be determined.…”
Section: Gst Gene Variantsmentioning
confidence: 99%
“…Previously, 8-OHdG levels were measured by HPLC with electrochemical detection (HPLC-EC) [ 70 ]; actually, ELISA kits detecting 8-OHdG are available allowing the use of this biomarker for investigating the OS involvement in many human diseases [ 72 ]. Additionally, in veterinary medicine, 8-OHdG is more and more assessed for evaluating OS-mediated DNA damage in either biotic or abiotic diseases [ 73 , 74 , 75 ].…”
Section: The Oxidative Profile and Its Alteration (Oxidative Stress) ...mentioning
confidence: 99%
“…10 Since neurodegenerative diseases display many similarities across species, our goal was to investigate 8-OHdG as a potential diagnostic biomarker that correlates with the histopathologic diagnosis of NAD/DM in the horse. The specific objectives of the study were (a) to optimize and validate a competitive ELISA previously reported in equids 14 for measuring 8-OHdG in equine serum and CSF and (b) to determine if measurable 8-OHdG in serum and CSF could aid in the antemortem diagnosis of NAD/DM. We hypothesized that 8-OHdG will be increased in serum and CSF from horses with NAD/DM compared with horses with other neurologic diseases, including cervical vertebral stenotic myelopathy (CVSM) and equine protozoal myeloencephalitis (EPM), and a control group of neurologically normal horses (control).…”
Section: Introductionmentioning
confidence: 99%